Demographics and outcome of histologically confirmed intracranial meningiomas. Issue 2 (19th December 2019) - Kamenova, Maria; Guzman, Raphael; Soleman, Jehuda
Objective: Meningiomas represent the most common intracranial extraaxial neoplasia in adults, accounting for a third of all diagnosed primary tumors of the brain. Despite decades of research, relatively little data on demographics of meningiomas exist. The aim of our study was to undertake an analysis of demographics and outcome of patients who underwent meningioma surgery over an 8-year time period at our institution. Methods: We reviewed 187 consecutive patients with histologically confirmed meningioma. Demographic data, tumor location and side, surgical resection grade, and histopathological and radiological data were collected and assessed for all patients. Furthermore, recurrence, morbidity, and mortality were evaluated. Results: Of the 187 consecutive patients undergoing meningioma resection over a period of 8 years, 131 (70.1%) were women ( p < 0.001). Meningiomas were classified as World Health Organization (WHO) grade I, grade II, and grade III in 66.8%, 31.0%, and 2.1%, of the cases, respectively ( p < 0.001). MIB-1 proliferation index was <1 in 7.5%, 1–5 in 52.9%, 6–10 in 22.4%, >10 in 11.8% of the lesions ( p < 0.001). In 82.4% of the cases, gross total resection was achieved. Recurrence occurred in 23 patients (12.3%), while overall morbidity and mortality rate was 41.2% and 7.7%, respectively. Conclusion: Based on our results, women are more than twice as likely to be affected, and the peak age is between 60 years and 70 years. Recurrence rate in our cohort was relatively low when compared to the data in the literature. The diagnosis of WHO grade II meningiomas, 31% in our cohort, is increasing since the 2007 WHO criteria have been published.